Underage Marriage from the Perspective of Islamic Family Law in Bireun Regency - Azhari Azhari (Civiliza Publishing, 2025)
The rise of underage marriages in North Aceh due to certain factors, causes them to marry at an early age. As happened in Peusangan District. The objectives of the study: (1) to describe the underlying practice of early marriage in Peusangan District, Bireuen Regency, (2) to describe the views of the people of Peusangan District, Bireuen Regency towards the practice of early marriage, (3) to describe the views of Islamic Law towards the practice of early marriage that occurs in Peusangan District, Bireuen Regency. This research is a field study using qualitative methods with normative, carried out in Peusangan District. Data collection techniques through interviews, observation and documentation. Data analysis techniques are carried out through data reduction, data presentation and data verification. The results of the study show that: (1) the practice of underage marriage in Peusangan District occurs due to economic factors, education level factors, family factors, child factors, social media factors, and promiscuity, the consequences are the rights and obligations as husband and wife, interrupted education, the birth of children, providing educational guarantees for children, poverty, and domestic violence (KDRT), (2) the view of the Peusangan community towards the practice of underage marriage is that it is permissible if there are positive impacts, such as avoiding immoral acts or the occurrence of something undesirable. However, it is not permissible if underage marriage brings a lot of harm, (3) the view of Islamic law towards the practice of underage marriage that occurs in Peusangan District, namely even though it is said that underage marriage is originally permitted according to Islamic jurisprudence, it does not mean that it is absolutely permitted for all women in all circumstances..